Tridax Procumbens Inhibitory Properties of Alpha Amylase - Kwesi, Akonu Adom Mensah Forson (International Journal of Biochemistry Advances, 2021)
The purpose of this study was to investigate the effects of extracts of Tridax procumbens leaves a traditional medicinal plant, on α-amylase activities in vitro. The air-dried aerial parts of Tridax procumbens leaves were extracted with Petroleum ether and Ethanol. The results of both enzyme inhibition activities were found in a dose-dependent manner. The strongest activity of α-amylase inhibition was found in Petroleum ether extract (IC50 = 10.436 mg/mL) followed by ethanol extract  (IC50 = 12.65 mg/mL) compared with acarbose having an IC50 value of 0.044 mg/mL. All extracts from this plant possess potent α-amylase activity inhibition which may offer a better therapeutic strategy to minimize postprandial hyperglycemia and its complications.
Keywords: Tridax procumbens; alpha-amylase activity; Diabetes Mellitus